Effects of blood pressure and heart rate circadian rhythms on left atrial function. Issue 11 (November 2021) - Zhao, Yixiao; Liu, Yan; Sun, Qiaobing; Han, Jiayu; Wei, Yushan; Lu, Yan; Zhang, Ying; Song, Wei; Cheng, Yunpeng; Cong, Tao; Jiang, Yinong
Abstract : Objective: We examined the associations among the circadian rhythms of blood pressure (BP), heart rate (HR) and left atrial function in essential hypertensive patients. Methods: The study included 237 essential hypertensive patients who completed 24-h ambulatory BP, HR monitoring and two-dimensional speckle tracking echocardiography (2DSTE). The strain and strain rate images were studied, and the following parameters were measured: left atrial reservoir strain and strain rate (LAS-S and LASR-S ), left atrial conduit strain and strain rate (LAS-E and LASR-E ), and left atrial booster strain and strain rate (LAS-A and LASR-A ). The left atrial stiffness index (LASI) was identified as the ratio of E / e ' to LAS-S . All participants were divided into three groups according to the percentage of nocturnal BP dipping (dippers, nondippers and reverse dippers). Results: The LASI was significantly higher in BP reverse dippers than in dippers and nondippers. LAS-S, LAS-E and LASR-E were significantly lower in BP reverse dippers than dippers and nondippers. Multivariate logistic regression analysis demonstrated that age, night-time mean SBP and the percentage of nocturnal HR decline were independently related to an increased LASI. Conclusion: Impairment of the left atrial reservoir and conduit functions was correlated with abnormal BP and HR circadian rhythms in hypertension. Increased left atrial stiffness was associated with night-time SBP and the percentage of nocturnal HR decline.